INDICATION OF SAFE POISON MATERiA^-S FROM INDIGENOUS PLANTS FOR CLEARING .UNWANTED FISHES FROM NURSERY PONDS - Shirgur, Girish A (Indian Journal of Fisheries, 2011)
Etadication of unwanted fishes is an essential prerequisite for ascientific management of perennial nursery ponds and stocking ponds. Routinenettings is'not a fool'pro